2020
DOI: 10.1007/s00381-020-04815-z
|View full text |Cite
|
Sign up to set email alerts
|

Presenting symptoms and time to diagnosis for Pediatric Central Nervous System Tumors in Qatar: a report from Pediatric Neuro-Oncology Service in Qatar

Abstract: Introduction There are no previous published reports on primary pediatric tumors of the central nervous system (CNS) in Qatar. We undertook this retrospective cohort study to review the diagnosis of CNS tumors in children in Qatar to analyze the presentation characteristics including symptoms, referral pathways, and time to diagnosis. Methods All children registered with Pediatric Neuro-Oncology service (PNOS) were included in the study. Data from the time of diagnosis (October 2007 to February 2020) were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
(51 reference statements)
1
21
1
Order By: Relevance
“…Prognostic assessment and risk of recurrence can be estimated from the analysis of Ki-67 markers and nuclear proliferation antigen (NPA), while p53 protein positivity is associated with lower survival rates disease free. 5 6 8 This explains why most of the studies 1 2 3 5 6 7 8 9 found are case reports and molecular studies, considering that new therapeutic tests are being developed, which made it difficult to correlate postoperative outcomes and long-term prognoses with those of our patient.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prognostic assessment and risk of recurrence can be estimated from the analysis of Ki-67 markers and nuclear proliferation antigen (NPA), while p53 protein positivity is associated with lower survival rates disease free. 5 6 8 This explains why most of the studies 1 2 3 5 6 7 8 9 found are case reports and molecular studies, considering that new therapeutic tests are being developed, which made it difficult to correlate postoperative outcomes and long-term prognoses with those of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,7,9 The therapeutic approach should be studied on a case-by-case basis, considering the different locations of these lesions. [2][3][4][5][6][7][8][9][10][11] However, studies 4,5,[9][10][11] suggest that radical resection followed by radiation in the entire neuroaxis is the mainstay of treatment, with better results when adding adjuvant chemotherapy. When used, the chemotherapeutic agents that have yielded the best therapeutic responses were CCNU (lomustina), vincristine, cisplatin, procarbazine, etoposide, temozolamide, cyclophosphamide, and carboplatin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations